Investigation on ethanolic stem extract of Ipomea sagittifolia to explore the presence of Saponins by High Performance Thin Layer Chromatography - Peeriga, Raveesha; Shaik, Karimulla; Shaik, Afsar; Riaz, Bushra; Raju, Gope Edward; Suresh, Subhasree Balamuruga (International Journal of Membrane Science and Technology, 2023)
Background: Saponins are a diverse group of naturally occurring plant compounds that play important roles in various aspects of plant physiology and ecology. An extract composed of several phytoconstituents may be easily analysed and interpreted using high performance thin layer chromatography (HPTLC) fingerprint analysis from a qualitative standpoint. Ipomea sagittifolia (Burn. f.) has a long history of use in traditional medical systems. Method: It was decided to interpret the phytoconstituents, namely the steroids in Ipomea sagittifolia (Burn. f.), in line with Current Good Manufacturing Practises, which highlight the significance of quality in relation to phytoconstituents, because HPTLC is a very trustworthy method of analysis. In this work, an HPTLC finger print profile for the saponins was made using an ethanolic extract of the stem of Ipomea sagittifolia (Burn. f.). This system includes the Scanner 4, TLC Visualizer, and Linomat 5 Applicator. Results: When phytoconstituents were evaluated using HPTLC densitometric screening at wavelengths of 366 nm and 540 nm, several peaks could be seen in the chromatogram. By analysing the peak regions, peak heights, and Rf values that were given in the proper tables, the phytochemicals are appraised. Conclusion: The study revealed the presence of saponins. This information is highly useful in studying chemical profiling and discovering bioactive components when the Rf values of these chemicals are compared with standards as a reference.